2010
DOI: 10.1007/s00018-010-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean neuropeptides

Abstract: Crustaceans have long been used for peptide research. For example, the process of neurosecretion was first formally demonstrated in the crustacean X-organ-sinus gland system, and the first fully characterized invertebrate neuropeptide was from a shrimp. Moreover, the crustacean stomatogastric and cardiac nervous systems have long served as models for understanding the general principles governing neural circuit functioning, including modulation by peptides. Here, we review the basic biology of crustacean neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
411
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 194 publications
(413 citation statements)
references
References 313 publications
(376 reference statements)
2
411
0
Order By: Relevance
“…Invertebrate nervous systems, including the crustacean stomatogastric nervous system (STNS), with its small number of large, uniquely identifiable neurons (Nusbaum et al, 2001;Skiebe, 2001;Nusbaum and Beenhakker, 2002;Fénelon et al, 2003;Fénelon et al, 2004;Hooper and DiCaprio, 2004;Marder and Bucher, 2007;Stein, 2009), have for many years provided important insights into our understanding of co-transmission (Kupfermann, 1991;Nusbaum et al, 2001;Nässel, 2009;Christie et al, 2010). In the present study, we identified the peptide co-transmitter in a pair of modulatory histaminergic projection neurons of the lobster STNS, then examined the roles played by this peptide and histamine in simultaneously modulating three different rhythmic motor patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Invertebrate nervous systems, including the crustacean stomatogastric nervous system (STNS), with its small number of large, uniquely identifiable neurons (Nusbaum et al, 2001;Skiebe, 2001;Nusbaum and Beenhakker, 2002;Fénelon et al, 2003;Fénelon et al, 2004;Hooper and DiCaprio, 2004;Marder and Bucher, 2007;Stein, 2009), have for many years provided important insights into our understanding of co-transmission (Kupfermann, 1991;Nusbaum et al, 2001;Nässel, 2009;Christie et al, 2010). In the present study, we identified the peptide co-transmitter in a pair of modulatory histaminergic projection neurons of the lobster STNS, then examined the roles played by this peptide and histamine in simultaneously modulating three different rhythmic motor patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with molecular biology and electrophysiology, single-cell MS is effective for examining neuronal architecture, and for delineating neuronal circuits that regulate physiology and control of instinctive and learned behaviors (Jarecki et al, 2010;Jing et al, 2010;Vilim et al, 2010). Investigations of signaling peptides and their involvement in neural plasticity, learning, memory, complex behavior, and various physiological functions at the level of the individual cell have been successful in invertebrate models (Jimenez et al, 1994;Christie et al, 2010;Li and Smit, 2010;Neupert and Predel, 2010;. Given the simplicity of their nervous systems and the accessibility of identifiable neurons, invertebrates provide unsurpassed single-neuron resolution and coupling to molecular mechanisms.…”
Section: Power Of One: Single-cell Analysis For Circuit and Pathway Cmentioning
confidence: 99%
“…In fact, little was known about the molecular machinery necessary for the establishment and proper functioning of neurochemical pathways in any crustacean. Although the molecules used for chemical communication are diverse in all multicellular organisms, peptides are by far the largest class used by nervous systems (Christie et al, 2010;Christie, 2011), and it is this group of compounds that was the first to be investigated via genome and/or transcriptome mining in Daphnia.…”
Section: Peptidergic Systemsmentioning
confidence: 99%
“…One factor that has surely contributed to this lack of neurochemical knowledge is its size; adults are typically just a few millimeters in overall length. This is surely true for the identification of its neuropeptides, as the standard method for peptide discovery until ~2005 was to isolate individual peptides chromatographically and/or biochemically from large pools of starting tissue and, upon their purification, assess their structures using a combination of proteolytic cleavage, Edman analysis and mass spectrometry (Christie et al, 2010). Given its minute size and the need to manually dissect a sufficient amount of starting material, the identification of even a single Daphnia neuropeptide via this strategy would surely have been daunting, as hundreds, and in some cases thousands, of central nervous systems (CNSs) were needed for the biochemical isolation and characterization of individual native peptides from much larger crustaceans (e.g.…”
Section: Introductionmentioning
confidence: 99%